2003
DOI: 10.1074/jbc.m304325200
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Specificity of Collagen Fibrillogenesis

Abstract: Suprastructures of the extracellular matrix, such as banded collagen fibrils, microfibrils, filaments, or networks, are composites comprising more than one type of macromolecule. The suprastructural diversity reflects tissue-specific requirements and is achieved by formation of macromolecular composites that often share their main molecular components alloyed with minor components. Both, the mechanisms of formation and the final macromolecular organizations depend on the identity of the components and their qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…In addition, collagen XI is expressed during development in a variety of tissues (30, 43, 44). Finally, collagen XI was shown to interact with collagen I to regulate fibril assembly in in vitro assays (45). This work demonstrated that collagens I and XI formed heterotypic fibrils and that in vitro co-assembly of collagens I and XI resulted in the assembly of smaller diameter fibrils.…”
Section: Tendon Structure and Function In A Col5a1 ϩ/ϫ Mature Mouse Mmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, collagen XI is expressed during development in a variety of tissues (30, 43, 44). Finally, collagen XI was shown to interact with collagen I to regulate fibril assembly in in vitro assays (45). This work demonstrated that collagens I and XI formed heterotypic fibrils and that in vitro co-assembly of collagens I and XI resulted in the assembly of smaller diameter fibrils.…”
Section: Tendon Structure and Function In A Col5a1 ϩ/ϫ Mature Mouse Mmentioning
confidence: 88%
“…Protofibril diameter also is a regulated by collagens V and XI. It is possible that collagens V and XI have different interactions with collagen I resulting in unique composite structures that would result in different fibril structures (45). A decrease in nucleation events and constant collagen I tissue content results in more collagen I assembled into each protofibril resulting in larger diameters.…”
Section: Collagens V and Xi Coordinately Regulate Fibril Nucleation Amentioning
confidence: 99%
“…Thus, collagen I/XI-fibrils are composites containing alloyed cores and sheaths of pure collagen I. Their final morphology is variable and depends on the collagenous composition [8]. Extrapolating this concept to banded fibrils in general, it has now become clear that the mixtures of fibrillar 188 D. E. Birk · P. Bruckner …”
Section: Polymerization Of Fibrillar Collagensmentioning
confidence: 98%
“…Types V and XI collagen molecules provide a template around which types I and II molecules aggregate to form fibrils (Eyre 2002, Hansen and Bruckner 2003, Wenstrup et al 2004, Wu et al 2009). Type V collagen is associated with type I collagen and type XI collagen with type II, but, as was mentioned above, some of the molecules are hybrid.…”
Section: Discussionmentioning
confidence: 99%